Management of Teaching Modules Based on Culturally Responsive Teaching Toward Education for Sustainable Development - Awiria, Awiria; Sukmanasa, Elly; Novita, Lina; Faridatul’al, Faridatul’al; Suhardi, Eka; Prawira, Asrori Yudha; Maesya, Aries (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2025)
The quality of learning materials that are not in accordance with the local culture affects the learning outcomes of students in elementary schools. This research aims to develop a responsive cultural teaching (CRT) learning module that is in accordance with the Independent Curriculum. The research method used is Research and Development (R&D) with the ADDIE model which includes analysis, design, development, implementation and evaluation. The subject of the study was a fourth-grade students of SD Negeri Julang Tanah Sareal. The results showed that CRT-based learning modules improved student learning outcomes with an average score of 4.1 in the indicators of knowledge and learning experience. In addition, the aspect of teacher support scored 4.04, and students' communication empathy skills scored 4.06, indicating that culture-based learning creates an inclusive and appropriate learning environment. This module also supports the formation of students' soft skills, such as collaboration and critical thinking, although the critical thinking aspect has not been improved. Finally, the development of CRT-based modules supports the implementation of Education for Sustainable Development (ESD) in primary schools, integrating local cultural values to create meaningful and sustainable learning experiences. This module is expected to be the basis for continuing education at the elementary level and can be replicated in a variety of other educational contexts